PRIVATE SECURITY COMPANIES AND THE DEONTOLOGICAL CODES - GABRIEL Jacek; KOŁODZIEJCZYK Adam (2018)
The article is an analysis of the private security companies’ activities, safeguarding people and property, in the context of compliance to ethical codes. The private security market in Poland was created last century in the eighties, and took over part of the tasks carried out thus far by the police and the army, which dealt with the protection of state institutions, and critical infrastructure of the country. The authors in their analysis point out that uniformed services, which previously dealt with protection, have had not only legal authorization in the implementation of such tasks, but also an extensive codes of honor, or ethical codes of conduct. Currently, there are few companies operating on the security market that have such codes of ethics. The authors suggest that the introduction of ethical (deontological) codes by private companies will increase the level of services provided, and contribute to the increase in the prestige of the protection profession.